Teachers’ Perceptions of Effective School Leadership in Moroccan Public Schools - El Hilali, Zakaria (International Journal of Language and Literary Studies, 2025)
This study explores public school teachers’ perceptions of effective school leadership in the Oriental Region of Morocco. As a data collection method, the study employed a qualitative online survey, which involved 110 public school teachers. Participants’ responses were thematically analyzed following Braun and Clarke’s six-phase process of thematic analysis. The findings show that principals have a significant influence on their schools, the learners, and the staff. They also reveal that effective school leaders are perceived as communicative individuals, relationship-focused, team oriented and collaborative. Having good administrative and managerial skills are necessary for effective leadership. However, these skills should be complemented a focus on relationships, communication, team building, and collaboration. Other attributes of effective school leadership include professionalism, fairness, consideration, and support. The findings highlight the importance of understanding leadership within its specific organizational and cultural context. Practical implications are suggested for leadership development in the context of Moroccan public schools.